SWOT Analysis of Account Officer Performance in BMT Mandiri Artha Syariah Bojonegoro - Shinta Abdul Rahman (JOURNAL OF SHARIA ECONOMICS, 2022)
Unfriendly and rude members faced by Account Officers in serving customers. Account Officers are required to think quickly in analyzing problems and must have a persuasive speaking style so members can feel safe. This study uses a type of qualitative research. This study uses data collection methods through interviews, observation, and documentation of the subject. The results of this study are Swot Analysis of the occount officer's performance in increasing the number of members, namely the strengths of providing financing to members, providing good promotions to members. The Occount Officer's threats to weaknesses are bad loans, opportunities for BMT are macroeconomic growth, the market is still open, supportive government policies, inter- and inter-agency cooperation for BMT, and public accountability for BMT. and threats, there is a lot of competition between bank and non-bank institutions. Existing competition includes Mandiri Syariah BANK, East Java BANK, Syariah Partner BANK, BMT Bina Insan Mandiri, and other financial institutions.